2018
DOI: 10.1186/s12987-018-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus crosses an in vitro human blood brain barrier model

Abstract: Zika virus (ZIKV) is a flavivirus that is highly neurotropic causing congenital abnormalities and neurological damage to the central nervous systems (CNS). In this study, we used a human induced pluripotent stem cell (iPSC)-derived blood brain barrier (BBB) model to demonstrate that ZIKV can infect brain endothelial cells (i-BECs) without compromising the BBB barrier integrity or permeability. Although no disruption to the BBB was observed post-infection, ZIKV particles were released on the abluminal side of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…In the current study, the ZIKV can cross brain endothelial cells and release of infectious virus particles, without an increase of endothelial monolayer permeability and no significant cytotoxicity in vitro (Figures 1, 2, 7). This is in agreement with previous studies showing the ZIKV crosses the BBB monolayer without the BBB barrier disruption (Papa et al, 2017;Alimonti et al, 2018). However, our studies showed that there were infectious atto647N-labeled virus particles that crossed the monolayer of BBB barrier cells in the presence of the treatment of endocytic inhibitors (Figures 7C,D), suggesting that we still cannot exclude the possibility that some viral particles selectively modulate tight junctions and cross the bottom chamber via paracellular diapedesis without overtly disrupting the BBB permeability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, the ZIKV can cross brain endothelial cells and release of infectious virus particles, without an increase of endothelial monolayer permeability and no significant cytotoxicity in vitro (Figures 1, 2, 7). This is in agreement with previous studies showing the ZIKV crosses the BBB monolayer without the BBB barrier disruption (Papa et al, 2017;Alimonti et al, 2018). However, our studies showed that there were infectious atto647N-labeled virus particles that crossed the monolayer of BBB barrier cells in the presence of the treatment of endocytic inhibitors (Figures 7C,D), suggesting that we still cannot exclude the possibility that some viral particles selectively modulate tight junctions and cross the bottom chamber via paracellular diapedesis without overtly disrupting the BBB permeability.…”
Section: Discussionsupporting
confidence: 93%
“…Disruption of the BBB enhances permeability of endothelial cell and is a hallmark of CNS infection (Daniels and Klein, 2015). However, recent studies reported that no barrier disruption was observed when ZIKV gained access to the CNS (Papa et al, 2017;Alimonti et al, 2018), suggesting that the endocytic transport system is required for the ZIKV to cross the BBB barrier. Given the existence of endosomal sorting pathways in different cell types, it is possible for the BBB cells to employ a similar process of endosomal transportation (Ayloo and Gu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, barrier disruption in this model occurred independent of changes to tight junctions and rather by a previously unknown mechanism of impairment in cellmatrix interactions [52]. iBMECs have also been used for revealing how Zika virus crosses the BBB through paracellular diapedesis to infect the CNS without compromising BBB integrity [53]. These studies highlight that iBMECs can be used to elucidate how human-specific pathogens traverse the BBB to colonize the CNS and could guide the development of new therapeutics to combat infection.…”
Section: Infectious Diseasementioning
confidence: 88%
“…These viruses can replicate in the CNS, cause encephalitis, and measurably affect BBB integrity (4449). In contrast, results from an in vitro BBB reconstitution model using a primary virus isolate from Thailand, and an interferon receptor-deficient murine model using Ugandan and Brazilian isolates suggests that a primary isolate of ZIKV doesn’t significantly disrupt the BBB to gain access to the CNS and that long-term damage to the BBB is minimal (50, 51). Similarly, productive ZIKV infection of human MECs in vitro does not result in cytopathic effects (44).…”
Section: Discussionmentioning
confidence: 99%